Arts Council Prepares For Ninth Performance Season (Raton, NM Raton Range, 1997)
This article is about the 9th performance season being sponsored by the Raton Arts and Humanities Council. Naming a few of the acts to come during this season.
Newspaper article
Master list item #: 130
File location is in the Raton file Cabinet
Keywords: Shuler Theater; Theaterworks/USA -- Performance Group; Creede Repertory Company -- Performance Group; Mac Frampton Trio -- Performance Group; Riverside Civic Light Opera -- Performance Group; Tucson Boys Choir -- Performance Group; Brigham Young University International Fold Dance Ensemble -- Performance Group; Old Pass Gallery; Music Performances; Theater Performances; Live Performances; Season Lineups; Raton, New Mexico